Managing Nordic Local Governments - Hlynsdóttir, Eva Marín; Hansen, Morten Balle; Cregård, Anna; Torjesen, Dag Olaf; Sandberg, Siv (Springer Nature, 2024)
This open access book examines the roles of municipal chief executive officers in Denmark, Finland, Iceland, Norway and Sweden. Whilst it has long been recognised that local authorities in these countries are often more autonomous than most other local authorities around the world, we still lack an integrated overview of leadership in Nordic local government, and the development of its top administrative management. This book ameliorates this lack of knowledge by providing a thorough, extensive and updated assessment of the role of municipal chief executive officers in the five Nordic states, as well as their interactions and relations with internal and external actors. Comparative in nature, it will appeal to all those interested in local and urban governance, public administration, public management, and leadership studies.